Dampak Kuliah Kerja Nyata Dalam Pengembangan Keagamaan Bagi Remaja - Cheni Eka Putri Wulandari; Sugiatno Sugiatno; Siswanto Siswanto (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The field work study can bring about new changes in society, and one of which is in the religious field. Thus, there will be an impact of field work study. As in the field work study held in Cawang Lama Village, students as the agents of change can make a real contribution to society through this program. Accordingly, this research aims to find out the impact of field work study on adolescents’ religious development in Cawang Lama Village. Religious development is supported by several factors, one of which is the field work study which has a very influential impact on society. The type of this research is field research with a qualitative descriptive approach. The object is Cawang Lama Village, and the subjects are adolescents. From this research, it is known that the field work study has a positive impact on adolescents’ religious development through the programs that have been implemented by students.